2015
DOI: 10.3390/antibiotics4040567
|View full text |Cite
|
Sign up to set email alerts
|

Co-Selection of Resistance to Antibiotics, Biocides and Heavy Metals, and Its Relevance to Foodborne Pathogens

Abstract: Concerns have been raised in recent years regarding co-selection for antibiotic resistance among bacteria exposed to biocides used as disinfectants, antiseptics and preservatives, and to heavy metals (particularly copper and zinc) used as growth promoters and therapeutic agents for some livestock species. There is indeed experimental and observational evidence that exposure to these non-antibiotic antimicrobial agents can induce or select for bacterial adaptations that result in decreased susceptibility to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
292
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(303 citation statements)
references
References 179 publications
(370 reference statements)
8
292
0
3
Order By: Relevance
“…This may be explained by the possibility that some of the identified heavy metal-resistance genes are inactive, either permanently due to the presence of mutation or facultatively (only in a particular host) as a result of genetic incongruity, which was previously shown for several other resistance module-bacterial host systems (Dziewit et al , 2015Romaniuk et al 2017). On the other hand, resistance phenotypes observed for strains without identified resistance genes could be "nonspecific" and resulted from, e.g., altered cell envelope permeability or biofilm formation (Wales and Davies 2015).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This may be explained by the possibility that some of the identified heavy metal-resistance genes are inactive, either permanently due to the presence of mutation or facultatively (only in a particular host) as a result of genetic incongruity, which was previously shown for several other resistance module-bacterial host systems (Dziewit et al , 2015Romaniuk et al 2017). On the other hand, resistance phenotypes observed for strains without identified resistance genes could be "nonspecific" and resulted from, e.g., altered cell envelope permeability or biofilm formation (Wales and Davies 2015).…”
Section: Discussionmentioning
confidence: 94%
“…To elucidate this problem, novel PCR primers should be designed, and this will be the aim of our future work. For the primer pairs specific to nccA and chrB genes, no PCR products were obtained, which might indicate that they are missing in the genomes of the studied bacteria, and the observed resistance phenotypes were driven by other systems or the resistance was rather "nonspecific" and resulted from, e.g., altered cell envelope permeability or biofilm formation (Wales and Davies 2015). This may also be the explanation for the As(III), As(V), Cd(II), Co(II), Cu(II), and Zn(II) resistance of strains in which the presence of specific genes involved in resistance to these metals, i.e., arsB, czcA, and copA, could not be shown by PCR screening.…”
Section: Distribution Of the Heavy Metal-resistance Genes In The Analmentioning
confidence: 98%
“…In fact, ARGs/ MRGs have long been reported to reside on MGEs, including genes with resistance to almost all antibiotic families that are embedded in gene cassettes on integrons (Gaze et al, 2011;Gillings et al, 2015;Wales and Davies, 2015;Di Cesare et al, 2016;Johnson et al, 2016), and multiple resistance genes for commonly consumed antibiotics and metals that are located on plasmids (Carattoli, 2009;Zhang et al, 2011;Popowska and Krawczyk-Balska, 2013;Wales and Davies, 2015;Johnson et al, 2016). However, there is a lack of general information regarding the cotransfer potential of ARGs and MRGs in different populations, particularly those that are seriously impacted by human activities.…”
Section: Transfer Potential Of Args and Mrgsmentioning
confidence: 99%
“…The above observed ARG and MRG abundance profiles within the genome collection, plus previous sporadic studies on coresistance in pathogens (Gillings et al, 2015;Wales and Davies, 2015;Di Cesare et al, 2016;Johnson et al, 2016) and the recently reported abundance correlation in clinically important genera (e.g., Escherichia, Shigella and Klebsiella) (Pal et al, 2015) kindled our interest in thoroughly investigating their possible physical genetic co-occurrence, particularly in humanassociated bacteria. Therefore, two concepts, the incidence of encountering ARGs along the distance from MRGs and their average minimum distance (MetA min ), were used to further evaluate the possible risk associated with ARG and MRG coselection by examining their likeliness of co-occurrence on Figure 1 Presence and absence of ARGs and MRGs in the complete genome collection.…”
Section: Co-occurrence Between Args and Mrgsmentioning
confidence: 99%
“…If biosecurity is poor on-farm, faecal droppings of wild birds may contaminate poultry feed and drinking water (Fogarty et al, 2003;Lévesque et al, 2000). Resistance to disinfectants often occurs in conjunction with ARGs (Bragg et al, 2014;Wales and Davies, 2015).…”
Section: Discussionmentioning
confidence: 99%